MOBILE CHASSIS FOR MECHANIZATION OF HARVESTING WORK IN INTENSIVE GARDENING (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
The article presents the development and evaluation of a mobile chassis designed to enhance the mechanization of harvesting operations in intensive gardening. Intensive gardening systems, characterized by high-density planting and optimized resource utilization, demand specialized equipment to streamline labor-intensive processes, particularly harvesting. This study focuses on designing a versatile and efficient mobile chassis capable of navigating the unique spatial constraints of intensive orchards. Key features of the proposed chassis include adjustable height and width for compatibility with various tree configurations, efficient maneuverability to reduce orchard soil compaction, and integration with harvesting tools to minimize fruit damage. The design prioritizes ergonomics and energy efficiency to improve productivity while addressing environmental sustainability. Field tests demonstrate the chassis's ability to significantly reduce manual labor, increase harvesting speed, and enhance the overall operational efficiency of intensive gardening systems. This innovation provides a practical solution to modern horticultural challenges, paving the way for improved profitability and sustainability in agricultural practices.